Hubungan Guru Profesional Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS di SMP Negeri 65 Bengkulu Utara - Hilyati Milla; Yolanda Dwi Kurnia (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to look at: 1) Professional Social Studies teacher class VIII at SMP Negeri 65 Bengkulu Utara, 2) student learning outcomes in social studies subject class VIII at SMP Negeri 65 Bengkulu Utara, 3) The relationship of professional teachers to student learning outcomes in subjects Social Studies Class VIII at SMP Negeri 65 Bengkulu Utara. This type of research is quantitative. Data collection techniques using questionnaires, observation, and documentation. The data analysis technique used in this research is statistical analysis using the following steps: Editing, scoring, and testing the hypothesis using the r product moment formula. After the data was collected and the research results were obtained as follows: 1) Professional Social Sciences teacher class VIII at SMP Negeri 65 Bengkulu Utara is 76.5 2) The average value of class VIII students in social studies subjects is 83.34 3) Professional teacher and student learning outcomes there is a significant relationship, professional teachers with student learning outcomes in social studies subjects with a relationship between the two variables of 20.1%, then 79.9% is determined by other factors.